Impact of plateau pika burrowing activity on the grass/sedge ratio in alpine sedge meadows in China - Yao, Xiang; Wang, Haoran; Zhang, Saiqi; Oosthuizen, Maria; Huang, Yilin; Wei, Wanrong (Frontiers in Plant Science, 2022)
Burrowing activities of plateau pikas cause widespread bare patches in alpine meadows on the Qinghai-Tibet Plateau, affecting the plant community composition and forage production. However, it is not clear how these bare patches influence the main forage composition in alpine meadows. Therefore, we investigated the plant communities in bare patches (BP) and neighboring control plots (CK) in alpine meadows in Maqu county in the Gannan region of China. Our results showed that plant communities in the CK plots differed from those in the BP plots. The sedge cover, number of sedge species and number of grass species were all significantly higher in the CK plots compared to the BP plots. However, grass cover and its dry weight were significantly higher in the BP plots. Grass cover and the grass dry weight in the BP plots were 1.859 times and 1.802 times higher than that in the CK plots across the five sites, respectively. Grasses also had a significantly higher cover and dry weight than sedge in the BP plots, grass cover was 66.5 times higher than the sedge cover, and the grass dry weight was 68.242 times that of the sedge dry weight. Therefore, bare patches resulting from plateau pika burrowing activity significantly increase the grass/sedge ratio in alpine meadows. A potential explanation is that grasses have a stronger reproductive potential than sedges in bare soil. This has implications for pasture yields since grasses have a higher biomass per unit area compared to sedges in alpine meadows.